Pemanfaatan Media Pembelajaran Interaktif Marvel Untuk Meningkatkan Minat Belajar Siswa SMA YPK Tabernakel Nabire Papua Tengah - Lalihatu, Marsya; Setiyanti, Angela Atik (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
The application of interactive media and the use of technology in supporting learning activities in schools is very important, but based on the initial interview with the Head of High School, YPK Tabernakel Nabire Central Papua, through the telephone in WA, the application of interactive learning media has not been thoroughly done. There are some obstacles, such as insufficient facilities, and not all teachers implement interactive learning media, resulting in a lack of interest among students in following the learning process. Based on this, the study aims to look at the use of Marvel as an interactive learning media to increase the interest of students in high school at YPK Tabernakel Nabire Central Papua, especially in class X MIA I. The research uses qualitative methods and purposive sampling techniques. The collected data will then be analyzed using one of the data analysis techniques of the Creswell Model. Based on the results of the observations and interviews, it is concluded that the interactive media of Marvel can increase the student's interest in learning, as seen from the indicators of the observation results and the source's answers during the interview.